Os desafios do ensino de PLE a estudantes búlgaros (fonética segmental e suprassegmental - Chergova, Vesela (Linguarum Arena, 2020)
This paper aims to present the specificity of teaching and learning Portuguese as a Foreign Language (PLE) in the academic context at Sofia University Sveti Kliment Ohridski. Taking into account the local tradition of teaching PLE and the students‘ results in the oral expression are intended to outline the critical areas in the acquisition of PLE by Bulgarian students. The most persistent errors are identified at the level of the Segmental and Suprasegmental Phonetics and working hypotheses for future research in this area are defined. It also seeks to study the application of digital resources, the internet and audiovisual media to stimulate students‘ self-motivation and emotional commitment to overcome the difficulties encountered in learning PLE.